The fight against illiteracy in the Semipalatinsk region in the 1920s: problems and results (Journal of history, 2024)
The article describes the reasons for the low literacy rate in the Semipalatinsk region in the first decade of Soviet rule. The study analyzes the main causes of the low level of illiteracy and also examines the various methods and approaches used by the authorities to overcome it. The role and importance of the literacy authorities established in the region were noted: the society «Down with illiteracy», the organization «Red Yurt», orphanages, educational centers, schools of the first stage, and the Kazakh pedagogical college.Quantitative and qualitative indicators of the level of illiteracy in the region have been determined based on materials from the funds of the Central State Archive of the Republic of Kazakhstan and the State Archive of the Abai region. The content and essence of instructions, information reporting letters, and reports of the departments of public education on the elimination of illiteracy are revealed. The literacy rate of the population and the number of educational institutions in the region are determined thanks to the materials of the population census, reports on the socio-economic development of the country, and statistical data.The authors concluded that it was not possible to solve the problem of eliminating illiteracy in the region by the decade of the October Revolution of the Soviet government due to objective and subjective reasons: poor financing of public education institutions, transfer of schools to public organizations, shortage of teaching staff, dependence of literacy elimination on the seasonality of agricultural activities, society's neglect of girls' education and the manifestation of the indifference of the population to the process of eliminating illiteracy. Measures to eliminate illiteracy in the Semipalatinsk region continued with the introduction of a system of «universal primary education» based on decisions taken by the party and state governing bodies in the early 1930s.Keywords: Semipalatinsk region, illiteracy, eradication of illiteracy, literacy center, school of the first stage, society «Down with illiteracy», red yurt, soviet education, educational system.